OBSERVATIONS ON THE MATURATION, FECUNDITY AND BREEDING OF THE COMMON CARP, CYPRINUS CARPIO LINNAEUS - Parameswaran, S; Alikunhi, K H; Sukumaran, K K (Indian Journal of Fisheries, 2011)
Observations made on the maturation, fecundity and breeding of the Chinese stock of the common carp, Cyprinus carpio var. communis in ponds at Cuttack are reported. The fish was found to attain maturity when six to eight months old, the males about two months earlier than the females and at a smaller size. Mature specimens of both sexes occur throughout the year, being maximum during late January to March and July to August.